(untitled) (Journal of Management and Social Sciences, 2016)
Contrary to the World Bank’s 1979 Berg’s recommendation that countries like Nigeria should focus more on funding primary rather than tertiary education, and the consequent ‘erratic’ funding allocation before 1999, the funding of higher education in Nigeria since 1999, though lower in comparison with other African nations, receives a much higher share of national resources. This is in addition to the encouragement and licensing of private universities and the establishment of the National Open University to increase access as well as enhance the delivery of tertiary education. Ironically, a cursory observation shows that, in spite of these modest attempts, students’ ‘brain drain’ seems to be on the increase. More and more Nigerian students are heading abroad to pursue undergraduate and graduate degrees. While recognizing the possible socio-economic background of these migrants, it is equally important to appreciate the economic and socio-political implications for the country and the continent – for now and in the future. Consequently, its the aim of the article to expose the possible negative consequences of students ‘brain drain’ in terms of the possible pitfalls of preferring the Diasporas to local experts in development purposes. It concludes that except this phenomenon is contained, through policies on attitudinal change, development and democracy would be difficult.